2009
DOI: 10.1097/hjr.0b013e3283312e94
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness matters more than physical activity in controlling cardiovascular disease risk factors

Abstract: PA and PF are inversely associated with the clustering of metabolic abnormalities. With regard to PA, it seems that intensity and more specifically higher intensity is the main characteristic of PA determining its effect on CVD RF. However, compared with PA, PF exerts greater effects on each of these individual CVD RF and its combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 34 publications
9
94
1
3
Order By: Relevance
“…The available data in this area suggests that CRF is the more clinically important predictor of CV and mortality outcomes 60,61 after controlling for CV risk factors. 62 However, it is important to consider (as stated in a recent review article by Blair et al 63 ) that much of the epidemiological data evaluating PA and CVD risk has been determined through self-report questionnaires whereas high CRF, after accounting for genetic heritability (which is extremely important), 64 is primarily determined by regular PA. Simply stated, CRF may be a better measure of habitual PA than are responses to self-report questionnaires.…”
Section: Is Pa or Crf Level The Best Predictor Of CV Mortality?mentioning
confidence: 99%
“…The available data in this area suggests that CRF is the more clinically important predictor of CV and mortality outcomes 60,61 after controlling for CV risk factors. 62 However, it is important to consider (as stated in a recent review article by Blair et al 63 ) that much of the epidemiological data evaluating PA and CVD risk has been determined through self-report questionnaires whereas high CRF, after accounting for genetic heritability (which is extremely important), 64 is primarily determined by regular PA. Simply stated, CRF may be a better measure of habitual PA than are responses to self-report questionnaires.…”
Section: Is Pa or Crf Level The Best Predictor Of CV Mortality?mentioning
confidence: 99%
“…In an observational study of 25,714 EUROPEAN ENDOCRINOLOGY adult men, low CRF was a strong and independent predictor of CVD and all-cause mortality in all BMI groups. 37 In an 8-year observational study of 21,925 men, unfit (low CRF), normal weight men had double the risk of all-cause mortality compared with fit, normal weight men (relative risk [RR] 2.07; p=0.01).…”
Section: The Role Of Adiposity In Type 2 Diabetesmentioning
confidence: 99%
“…Several studies suggest that CRF is more important than PA in predicting CV and all-cause mortality. 24,25 A large cohort study (31,818 men and 10,555 women) found that CRF was more strongly associated with all-cause mortality than was PA. The authors concluded that the stronger associations with CRF were most likely due to inherent error and misclassification in self-reported PA. 26 However, a meta-analysis of 23 sex-specific cohorts of PA or CRF (representing 1,325,004 person-years of follow up) attempted to correlate PA and CRF and concluded that while the two are related, there is a poor correlation between PA and CRF, particularly at low fitness levels.…”
Section: Which Is More Important -Cardiorespiratory Fitness or Physicmentioning
confidence: 99%
“…Although CRF is hereditary to a large extent, physical training and exercise can increase CRF which is known to mediate the effects of PA on adiposity and cardiometabolic biomarkers in adults [3,4]. In fact, it has been shown that improvement in CRF can lower allcause mortality and cardiometabolic risk without a reduction in body weight or adiposity in adults.…”
mentioning
confidence: 99%